Toxicity evaluation and medical application of multi-walled carbon nanotubes - Zhou, Lulu (Cranfield University, 2015)
Carbon nanotubes (CNTs) are of special interest to industry and they have been increasingly utilised as advanced nanovectors in drug/gene delivery systems. They possess significant advantages including high surface area, welldefined morphologies, unique optical property, superior mechanical strength and thermal conductivity. However, despite their unique and advanced physicochemical properties, the low compatibility of some of those materials [e.g. multiwalled CNTs (MWCNTs)] in most biological and chemical environments has also generated some serious health and environment concerns. Chemical functionalization broadens CNT applications, conferring new functions, and at the same time was found potentially altering toxicity. Although considerable experimental data related to functionalised CNT toxicity, at the molecular and cellular levels, have been reported, there is very limited information available for the corresponding mechanism involved (e.g. cell apoptosis, genotoxicity. The toxicity of carbon nanotubes has been confirmed on many cell lines including A549 (lung cancer cell line) and MRC-5 (lung fibroblasts). However, the sensitivity of each cell line in terms of cellular morphology, apoptosis and DNA damage are still unknown. In this report the different levels of cellular response to oxidative stress and phagocytosis have been investigated in A549, MCF-7 and MRC-5 cell lines to better understand the mechanisms of the toxicity pathway. siRNA as an ideal personalized therapeutics can specifically regulate gene expression, but efficient delivery of siRNA is difficult while it has been shown that MWCNTs protect siRNA, facilitate entry into cells. In this study, we comprehensively evaluated the in vitro cytotoxicity of pristine and functionalized (-OH, -COOH) multi-wall carbon nanotubes (MWCNTs), via cell viability test, reactive oxygen species (ROS) generation test, cell apoptosis and DNA mutation detection, to investigate the non-toxic dose and influence of functional group in A549, MCF-7 and MRC-5 cells exposed to 1-1000 μg/mL MWCNTs from 6 to 72 hours. In addition, 84 toxicity related genes have been detected to investigate the change of RNA regulation after treatment with MWCNTs. The research findings suggest that functionalized MWCNTs are more genotoxic compared to their pristine form, and the level of both dose and dispersion in the matrix used should be taken into consideration before applying further clinical applications of MWCNTs. Among all three cell lines, MCF-7 was the most sensitive to cell death and DNA damage induced by pristine carbon nanotubes. The majority of MCF-7 cell death was in necrotic. In A549 cells, apoptosis played a notable role in cytotoxicity. MRC-5 didn’t show significant cell loss or membrane damage, which might be explained by its low cell growth rate, notably however, a great reduction of the F-actin and attachment points was observed after treatment which indicates that MRC-5 cells are under very unhealthy condition and less attached to the bottom of flasks. Despite their toxicity, which is still being researched, carbon nanotubes have a great potential in clinical medicine. Thus, understanding the sensitivity of different cell lines could offer a more individualized approach for future treatment regimes. In regards to gene delivery, MWCNTs were found to be less toxic than chemical agents (positive control) without weakening the delivery efficiency, which proves that MWCNTs have a good potential in medicine area.
Keywords: Multi-walled carbon nanotubes; characterization; aggregation; functionalization; cytotoxicity genotoxicity siRNA delivery; cell lines